Sanksi terhadap Praktik Bullying di Pesantren Kota Padangsidempuan - Seva Mayasari; Toguan Rambe (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
Bullying is an event that is so worrying because it occurs in educational institutions such as Islamic boarding schools. The background to the occurrence of bullying is due to the different characters of the students, their age or level of education, and the culture of their family origin. With these various differences in the background, life in Islamic boarding schools is full of diversity, but problems can also arise, one of which is bullying. The location of this research is at the Padang Sidempuan Islamic Boarding School, namely Al Ansor Padangsidempuan Islamic Boarding School and Darul Ikhlas H. Abdul Manap Siregar Padang Sidempuan Islamic Boarding School. This study aims to find out how bullying occurs in Islamic boarding schools in Padang Sidempuan City and how to deal with it. Data collection techniques used were observation, interviews, focus group discussions (FGD), and documentation. Data analysis is used with qualitative descriptive analysis. The results of this study show that the forms of bullying that occur are physical bullying, verbal bullying, psychological bullying, and social bullying. To deal with bullying that occurs in Islamic boarding schools, those schools carry out two actions: first, preventive action, which consists of Islamic boarding school religious activities; and second, repressive action, which means that if there is a complaint of bullying, the person concerned will be called to the BK room and processed. If proven guilty, sanctions will be given according to what was violated. The sanctions given are in accordance with what was agreed upon at the beginning of entering the hut. Starting from physical sanctions, summoning parents, even expulsion from the hut. So far, the two Islamic boarding schools have never reached the realm of the law (court). Most are resolved amicably or according to the rules that apply in Islamic boarding schools.